Environmental Factors Affecting the Crops’ Growth and Development: An Analytical Study - BHARDWAJ, RAJNEESH (International Journal of Psychosocial Rehabilitation, 2024)
Environmental elements have a vital role to play in the cultivation and maturation of crops. It is essential to comprehend these factors to augment crop output and eminence. A detailed analysis has been conducted to investigate the effects of distinct environmental components on crop growth and development. These factors encompass temperature, illumination, water, soil, and atmospheric gases. Temperature influences the rate of photosynthesis and respiration, which, in turn, impact crop growth and development. Illumination is a prerequisite for photosynthesis and influences the physical structure, growth, and yield of plants. Water supply is a crucial factor in the growth of plants, and soil conditions can impact the nutrition of plants and the development of roots. Atmospheric gases, such as carbon dioxide, nitrogen, and oxygen, impact the physiology and growth of plants. Environmental factors can also give rise to abiotic pressures like drought, inundation, and salinity, which may restrict crop output and quality. Familiarity with the implications of environmental elements on crop growth and development can facilitate farmers in optimizing crop production and augmenting yield and quality while curbing environmental degradation.